Dampak dan Manfaat Pembelajaran Daring dalam Proses Pembelajaran Pendidikan Agama Katolik dan Budi Pekerti Pada Sekolah Katolik di Kota Samarinda - Carolina Bulan (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2022)
This research describes the positive and negative impacts and benefits of online learning in Catholic Religious Education and Moral Education subjects for teachers, students, and parents at SDK 1 WR. Soepratman Samarinda. This qualitative study used data collection techniques, namely interviews, observation, and documentation, to collect data from 10 informants: one principal, a teacher, four students, and four parents. The results of the study show that in the online learning process, there are positive and negative impacts that affect smooth learning, namely, teachers and students are not all proficient in using technology, students do not have learning facilities, and learning activities are carried out in the network. So, parents help children in launching learning activities by seeking learning tools. The benefits of online learning for teachers are taking advantage of technology, managing time management, finding supporting sources, delivering material quickly, and keeping up with the times. The benefits for students are being able to study anywhere, anytime with anyone, make study schedules, seek information, and establish good relations with parents. The benefits for parents are participating in learning with children, establishing good social relations, being educators, being friends, being a family for children, and working with teachers.